The Ties that Bind : Measuring International Bond Spillovers Using Inflation-Indexed Bond Yields - Swiston, Andrew (IMF Working Papers; Working Paper, 2007)
This paper explores international bond spillovers using daily and intra-day data on yields on inflation-indexed bonds and associated inflation expectations for the United States, Australia, Canada, France, Sweden, Japan, and the United Kingdom. The analysis starts in 2002, by which point U.S. inflation-indexed markets were fully mature. Real bond yields are found to be closely linked across countries, with developments in U.S. markets determining around half of real foreign yields and no evidence of spillovers back to the United States. Spillovers in inflation expectations are smaller and the direction of causation is less clear.